Habitat Suitability Modeling to Identify the Potential Nursery Grounds of the Atlantic Mackerel and Its Relation to Oceanographic Conditions in the Mediterranean Sea - Giannoulaki, Marianna; Pyrounaki, Maria M.; Bourdeix, Jean-Herve; Ben Abdallah, Lotfi; Bonanno, Angelo; Basilone, Gualtiero; Iglesias, Magdalena; Ventero, Ana; De Felice, Andrea; Leonori, Iole; Valavanis, Vasilis D.; Machias, Athanassios; et al. (Frontiers in Marine Science, 2017)
Our knowledge for the distribution of Atlantic mackerel (Scomber scombrus) in the Mediterranean Sea is very limited and fragmented. In the current work habitat suitability modelling was applied to summer acoustic surveys data of Atlantic mackerel juveniles derived from the north part of the Mediterranean (i.e. acoustic data from the Gulf of Lions, pelagic trawls held during acoustic surveys in Spanish Mediterranean waters, south Adriatic Sea, Strait of Sicily and North Aegean Sea) using generalized additive models along with satellite environmental and bathymetry data. Bathymetry along with sea surface temperature and circulation patterns, expressed through sea level anomaly and the zonal component of the absolute geostrophic velocity, were the variables found important. The selected model was used to produce maps presenting the potential nursery grounds of Atlantic mackerel throughout the Mediterranean Sea as a measure of habitat adequacy. However, the assessed potential nursery grounds were generally marked as “occasional”, implying that although there are areas presenting high probability to encounter Atlantic mackerel, this picture can largely vary from year to year stressing the high susceptibility of the species to environmental conditions. In a further step and towards a spatial management perspective, we have estimated and visualized the overlap between Atlantic mackerel and anchovy/ sardine juvenile grounds throughout the basin. Results showed that although the degree of overlapping was generally low, not exceeding 15 % in general, this varied at a regional level going up to 30%. The potential of the output of this work for management purposes like the implementation of spatially-explicit management tools is discussed.